REPRESENTASI POLITY DAN TRIVIA DALAM AGENDA MEDIA (Studi Agenda Media SK Ibukota) - Ari Cahyo Nugroho (BPSDMP Kominfo Jakarta, 2015)
ABSTRACT This content analysis research deals with the representation of ‘polity and trivia’ issues in media agenda from capital city newspapers. This issue is from the emergence phenomenon of trivia issue in media agenda, incidentally,it should ideally appear through the nature of the polity issues. This research seeks to discover ‘how’ the representation of polity and trivia issue in media agenda from capital city newspapers. Based on the research results, through the method of content analysis, it concluded that the representation of media agenda ‘polity and trivia issue’ in newspaper, can beexpressed in agenda setting theory throught the concept of agenda. Regarding the emergence of the trivia issue, in the dominance of media polity in issues agenda, other than to justify the truth of agenda setting theory; this also indicates the truth of catharsis hypothesis, that with scheduled trivia issue, editorial media organization will have a positive effect, also for the audience. In the future, for the development of the agenda media theory, researchers should develop his/hers analysis, such doing a trial ‘difference’ test between samples, related to media agenda. And also ‘performs a deepening’ related to the agenda in the trivia issues agenda relationship. Key Words: Representation; Media Agenda ; Polity; Trivia. ABSTRAK Penenelitian konten analysis ini mempermasalahkan representasi isu polity dan trivia dalam agenda media suratkabar Ibukota. Permasalahan ini sendiri berangkat dari fenomena munculnya isu trivia dalam pengagendaan media, yang nota bene di sisi lain idealnya muncul melalui isu-isu bersifat polity. Penelitian ini berupaya menemukan bagaimana representasi isu polity dan trivia dalam agenda media suratkabar Ibukota. Berdasarkan hasil penelitian melalui metode content analysis, disimpulkan bahwa representasi isu polity dan trivia dalam pengagendaan media suratkabar itu menjadi justifikasi akan kebenaran yang dikemukakan dalam teori agenda setting menyangkut konsep agenda Mengenai munculnya isu trivia dalam dominasi isu polity dalam pengagendaan media, selain dengan sendirinya membenarkan kebenaran asumsi theory agenda setting, ini juga mengindikasikan kebenaran akan hipotesis katarsis, bahwa dengan mengagendakan isu trivia itu, organisasi redaksi media berharap akan memiliki efek positif juga bagi para audience. Untuk pengembagan teori agenda media ke depan, hendaknya peneliti itu melakukan pengembangan analisisnya yang diantaranya melakukan uji-uji beda di antara sampel menyangkut pengagendaan media. Selain itu juga melakukan pendalaman terkait dengan pengagendaan dalam hubungan pengagendaan isu-isu trivia. Kata-Kata Kunci : Representasi; Agena Media; Polity; Trivia.